Mobile Phone Addiction Among Children and Adolescents: A Systematic Review. Issue 4 (October 2019) - Sahu, Maya; Gandhi, Sailaxmi; Sharma, Manoj Kumar
Abstract: Objectives: Mobile phone addiction among children and adolescents has become a concern for all. To date, focuses have been given to Internet addiction, but comprehensive overview of mobile phone addiction is lacking. The review aimed to provide a comprehensive overview of mobile phone addiction among children and adolescents. Methods: Electronic databases search included Medline, Proquest, Pubmed, EBSCO host, EMBASE, CINAHL, PsycINFO, OVID, Springer, Wiley online library, and Science Direct. Inclusion criteria were studies including children and adolescents, studies published in peer-reviewed journals, and studies focusing on mobile phone addiction or problematic use of mobile phone. A systematic search identified 12 descriptive studies, which met inclusion criteria, but no interventional study met the criteria. Results: The prevalence of problematic mobile phone use was found to be 6.3% in the overall population (6.1% among boys and 6.5% among girls), whereas another study found 16% among the adolescents. The review finds that excessive or overuse of mobile phone was associated with feeling insecurity; staying up late at night; impaired parent–child relationship; impaired school relationships; psychological problems such as behavioral addiction like compulsive buying and pathological gambling, low mood, tension and anxiety, leisure boredom, and behavioral problems, among which most pronounced association was observed for hyperactivity followed by conduct problems and emotional symptoms. Conclusions: Though mobile phone use helps in maintaining social relationship, mobile phone addiction among children and adolescents needs urgent attention. Interventional studies are needed to address these emerging issues.